THE IMPACT OF DECISION POWER ON FINANCIAL RISK TOLERANCE AND ASSET ALLOCATION ON HOUSEHOLD - Anne Rumondang Malau; Halomoan Sihombing (JURNAL ILMIAH MAKSITEK, 2018)
This study considers the impact of decision power and demographic variable on risk tolerance and portfolio in households. Financial management in the household becomes an important issue in creating community welfare. Married Couple (N= 154) separately completed a survey using Decision Power Index by Blood and Wolfe, The Survey of Consumer Finances risk tolerance question, demographic information such as, age, education level, gender, working status, and tribe. The study found that effect of decision power for husband and finance and portofolio risk level, Suggesting that husband more affects to take financial decision, but Age and Education of spouse was found to be a significan factor in risk tolerance. Further, a tribe indicating the decision power, risk tolerance level among spouse in household.